Tony Award Season 2017 [compact disc]. - Finn, William; Lloyd Webber, Andrew, 1948-; Malloy, Dave, 1976-; Schönberg, Claude-Michel; Sankoff, Irene; Lloyd Webber, Andrew, 1948- (Broadway Records, 2017)
The first ever Tony Award Season compilation album. Each musical from the 2016-2017 season, including the 2017 Tony-nominated musicals, have been invited to contribute a song to this compilation album.